Pathological gambling after bilateral subthalamic nucleus stimulation in Parkinson disease - Smeding, H M M (BMJ Group, 2007)
We describe a patient with advanced Parkinson's disease who developed pathological gambling within a month after successful bilateral subthalamic nucleus (STN) stimulation. There was no history of gambling. On neuropsychological testing, slight cognitive decline was evident 1 year after surgery. Stimulation of the most dorsal contact with and without medication induced worse performances on decision making tests compared with the more ventral contact. Pathological gambling disappeared after discontinuation of pergolide and changing the stimulation parameters. Pathological gambling does not seem to be associated with decision making but appears to be related to a combination of bilateral STN stimulation and treatment with dopamine agonists.